Women Participation in Local Development: A Study of Kaski District - Dahal, Girdhari (Journal of Political Science, 2021)
The purpose of this study is to examine the women participation in local development of Kaski district in Nepal. The nation provides equal opportunities to the women. Despite that, they are strong enough and empowered in local development? Nepalese women are struggling for equal opportunity in society. This paper is qualitative research. It is based on primary and secondary data based on descriptive and analytical paper. In the local election held in 2017, 152 women were elected to the local government in Kaski district. They are Dalit and non-Dalit both. Constitutionally thirty-three percent women are required to be the participants on each level of the government of Nepal. It is a legal provision for participation in local governments. Similarly, women are the participants in the federal, provincial and local governments of Nepal. The constitution has provided women participation on policy level as well as civil service, Nepal Police and Nepal Army and other sectors of the nation. Now, the federal democratic republic nation of Nepal has been practicing inclusive democracy. It is a great achievement for the Nepalese women. Now, 21th century as democratic country like Nepal needs meaningful women participation on a local level. The women need equal opportunity in the social, economic and political sector. Local level of Kaski district women participate with empower on politics as well as development activities as planning, budgeting, judicial leadership. These are the symbolic empowerment of women in local development.